Crystallization of metals and alloys. Problem. Solutions - E. I. Marukovich; V. Yu. Stetsenko (Литьë и металлургия)
For a solution of the problem of crystallization of metals and alloys it is necessary to take for granted that the basic construction elements in forming crystals are nanocrystals of phases. Specific interphase surface energy of a crystallization center is directly proportional to its radius. Hydrogen exerts direct impact on process of crystallization of dendritic crystals of phases.